The efficacy of resveratrol in the treatment of liver fibrosis: a systematic review and meta-analysis of preclinical studies - Luo, Dehua; Shang, Zhoubiao; He, Qingying; Ke, Jianlong; Xian, Qiqi; Dai, Shunxin; Sun, Sheng; Xiong, Shaoquan (Frontiers in Nutrition, 2025)
ObjectiveTo evaluate the effects and underlying mechanisms of resveratrol—a plant-derived polyphenol abundantly found in natural dietary sources such as grapes and blueberries—on the amelioration of liver fibrosis.MethodsData were obtained from a systematic review of 46 animal studies identified across seven databases. Study quality was assessed using the SYRCLE tool for risk of bias. Meta-analysis was performed with Stata 17.0. Outcome measures included collagen deposition, hydroxyproline content, extracellular matrix components (HA, LN, CIV, PIIINP), key fibrogenic mediators (TGF-β, α-SMA, Col1α1), liver function markers (albumin, ALT, AST, ALP), as well as inflammatory and oxidative stress indicators.ResultsResveratrol markedly attenuated collagen deposition and reduced hydroxyproline levels, a central marker of fibrotic progression. It significantly inhibited the accumulation of extracellular matrix components and modulated profibrotic mediators. Improvement in liver function was indicated by elevated albumin levels and decreased activities of ALT, AST, and ALP. Mechanistically, resveratrol exerted dual modulation through the following pathways: Inflammatory pathways: downregulation of IL-6 and TNF-α; Oxidative stress responses: enhancement of SOD and GSH activities, accompanied by reduction in MDA levels.ConclusionResveratrol significantly alleviates liver fibrosis in animal models via anti-inflammatory and antioxidant mechanisms. However, translation to clinical practice requires further validation owing to interspecies differences and notable heterogeneity across included studies. Standardized preclinical study designs and cross-species mechanistic investigations are warranted to support future clinical applications.Systematic review registrationThe registered website: https://www.crd.york.ac.uk/PROSPERO/view/CRD42025633941.